Seroprevalence of syphilis and herpes simplex virus type 2 and its association with sexual behaviour factors (a cross-sectional study among men who have sex with men in Manado, Indonesia) - Niode, Nurdjanah J.; Minarto, Hendra; Mitaart, Andravita F.; Kapantow, Grace M.; Kandou, Renate T. (Journal of General - Procedural Dermatology and Venereology Indonesia, 2017)
Aims: This study investigated the seroprevalence and sexual risk behavior factors associated with syphilis and herpes simplex virus type 2 (HSV-2) among men who have sex with men (MSM), in Manado, Indonesia. Methods: Serum samples and questionnaires regarding their socio-demographic and sexual behaviour were collected from 60 MSM in Manado. Samples were screened for anti-HSV-2 IgG for herpes, the Venereal Disease Research Laboratory (VDRL) and the Treponema Pallidum Haemagglutination (TPHA) test for syphilis. A cross sectional method was used in this study.  Results: Of 60 MSM (median age was 20 years), 35% had homosexual orientation and 65% had bisexual orientation. First sexual intercourse of most participants (48.3%) within 16 to 18 years old. In the last 12 months, most participants (55%) had only one male sex partner. There were 63.3% and 16.7% participants performed oral and anal intercourse. About 23.3% participants used condom consistently, but only 35.7% used compatible lubricant. Seropositivity of VDRL and TPHA was detected in 5% participants and anti-HSV-2 IgG in 23.3% participants. The positive serology test for syphilis was associated with sexual intercourse mode (p= 0.001). Significant association was found between anti-HSV-2 IgG seropositivity and condom-use behaviour (p=0,028). Conclusions: The study demonstrated 5% and 23.3% positivity of serology test for syphilis and anti-HSV-2 IgG respectively. Seropositivity of syphilis was correlated with oral and anal intercourse while HSV-2 with no condom-use behaviour among MSM in Manado, Indonesia.